THE INFLUENCE OF ISLAMIC BRANDING, RELIGION, AND PRODUCT DIVERSITY ON CONSUMER PURCHASE DECISIONS (STUDY AT 212 CONDET MART, EAST JAKARTA) - Fildzah Karisma Paradasa; Puspita Puspita (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2022)
The presence of halal minimarkets is known to have increased based on the number of consumption of Indonesian halal food products in 2018 and 2019. This shows that the potential for halal minimarket business activities is quite high, seeing the phenomenon of halal trends, especially public consumption of halal products which continues to increase and the majority of the population is Muslim in domestic. However, until now 212 Mart outlets have not been found as many as conventional minimarkets which are already known to the public. Thus, this study aims to see the effect of Islamic branding, religiosity, and product diversity on consumer purchasing decisions (study at 212 Mart Condet, East Jakarta). This research is a quantitative research with data collection techniques using offline questionnaires. The analysis method used is multiple regression analysis and processed with the SPSS 21 program. The research sample is 100 consumers who have shopped at 212 Mart Condet, East Jakarta. The results show that there is an effect of Islamic Branding on consumer purchasing decisions 212 Mart Condet, there is no religious influence on consumer purchasing decisions 212 Mart Condet, and there is an influence of product diversity on consumer purchasing decisions 212 Mart Condet